Report of the conference "Connecting Tamás Varga’s Legacy and Current Research in Mathematics Education": November 6-8, 2019, Budapest, Hungary - Artigue, Michèle; Gosztonyi, Katalin; Kónya, Eszter; Vancsó, Ödön (Teaching Mathematics and Computer Science, 2020)
On the occasion of the 100th anniversary of the birth of the Hungarian mathematics educator, didactician and reform leader Tamás Varga, a conference on mathematics education has been organized in November 2019 and held at the Hungarian Academy of Science.